Pengaruh Pemberian Tepung Sorgum sebagai Pengganti Tepung Jagung terhadap Produksi Karkas dan Non Karkas Ayam Broiler Fase Grower: The Effect of Sorgum Flour as A Substitute for Corn Flour on Carcas and Non-Carcas Production of Broiler Chickens in the Grower Phase - Lete, Agustinus Nudu; Malik, Agustinus Konda; Sinlae, Markus (Universitas Nusa Cendana, 2024)
The experimen aims to examine the response of providing sorghum flour as a substitute for corn flour on carcass and non-carcass production of broiler chickens. The experimen was carried out in the livestock workshop pen for five weeks starting from February 20 to March 26 2024. This exploration design used a RAL design consisting of four treatments and was repeated 5 times for each treatment, making 20 experimental units. The research treatment was P0:54% corn in the ration without sorghum as a control. P1: 25% sorghum as a substitute for corn in the ration, P2: 50% sorghum as a substitute for corn in the ration, P3: 75% sorghum substitute for corn in the ration. The ANOVA results show that the response to giving sorghum flour as a substitute for corn flour in the ration of grower phase broiler chickens was significantly significant (P<0.05) in the non-carcass percentage and not significant (P>0.05) in the final body weight, carcass percentage, and percentage abdominal fat. It was concluded that sorghum could replace 75% of the portion of corn used in rations. ABSTRAK Penelitian ini bertujuan untuk mengkaji respon pemberian tepung sorgum subtitusi tepung jagung pada produksi karkas dan non karkas ayam broiler. Penelitian dilaksanakan di kandang workshop peternakan selama lima minggu terhitung dari tanggal 20 Februari sampai dengan 26 Maret 2024. Percobaan menggunakan rancangan rancangan acak lengkap, terdiri atas empat perlakuan dan diulang 5 kali tiap perlakuan jadi 20 unit percobaan. Perlakuan penelitian yaitu P0:54% jagung dalam ransum tanpa sorgum sebagai kontrol. P1: 25% sorgum sebagai pengganti jagung dalam ransum, P2: 50 % sorgum sebagai pengganti jagung dalam ransum, P3: 75 % sorgum subtitusi jagung dalam ransum. Hasil anova terlihat respon pemberian tepung sorgum sebagai pengganti tepung jagung dalam ransum ayam broiler fase grower nyata signifikan (P<0,05) pada persentase non karkas dan tidak signifikan(P>0,05) pada bobot badan akhir, persentase karkas, dan persentase lemak abdominal. Disimpulkan bahwa sorgum dapat mengganti 75% dari porsi penggunaan jagung dalam ransum.